Effect of Tax Rates on the Growth of Small and Medium Enterprises in Kisumu County, Kenya - Madara, George Otieno; Ghabon, Yasin Kuso (International Journal of Multidisciplinary Approach Research and Science, 2025)
Small and Medium Enterprises (SMEs) are critical to Kenya’s economy, driving employment and GDP growth. In Kisumu County, high tax rates, including turnover tax (3%), corporate income tax (30%), and value-added tax (VAT, 16%), pose significant barriers to SME growth. This study investigates the effect of tax rates on SME growth, focusing on profitability, customer base expansion, and operational scalability. Guided by the Economic Deterrence Theory, Ability-to-Pay Principle, and Resource-Based View, a correlational research design was employed, targeting 1,200 registered SMEs in Kisumu County. Using stratified random sampling, a sample of 291 SMEs was selected, with data collected from 262 respondents (90% response rate) via structured questionnaires with a five-point Likert scale. Validity was ensured through content and construct alignment, with reliability confirmed by a Cronbach’s alpha of 0.83. Descriptive statistics (means, frequencies, standard deviations) and inferential statistics (correlation, regression) were analyzed using SPSS version 26. Findings revealed a strong negative correlation (r = -0.645, p < 0.001) between tax rates and SME growth, with regression results indicating a significant negative effect (β = -0.435, p < 0.001). High tax rates increased operational costs (mean = 4.02, SD = 0.95), reduced profitability (mean = 3.98, SD = 0.97), and limited reinvestment (mean = 3.92, SD = 1.01). Challenges such as compliance costs and policy uncertainty were noted. The study concludes that high tax rates significantly hinder SME growth by constraining financial resources. Recommendations include revising tax rates, simplifying compliance, enhancing tax education, and introducing incentives to foster SME growth.